The Social Criticism in the Film Capernaum by Nadine Labaki Through Charles Sanders Peirce’s Semiotic Framework - Muhammad Haritsah Rais; Rohanda Rohanda (Gunung Djati Conference Series, 2025)
Film has the ability to convey implicit messages through its visual imagery. Capernaum, therefore, presents various forms of criticism, values, and norms. Directed by Nadine Labaki, this film portrays powerful messages of humanity and offers sharp social criticism in response to the realities faced by marginalized communities in large cities. The purpose of this study is to examine the social criticism presented in the film Capernaum. This research employs a qualitative descriptive method, as well as a quantitative approach, based on Charles Sanders Peirce’s semiotic theory. The researcher will carefully select specific scenes that reflect the concept of self-meaning. These scenes will then be analyzed in terms of their meaning through the components of sign, object, and interpretant as found in the film. The findings of this research reveal that Capernaum contains various forms of social criticism, including criticism of child exploitation, structural poverty, social class inequality, domestic violence, and the involvement of children in drug trafficking